2020
DOI: 10.1155/2020/5169278
|View full text |Cite
|
Sign up to set email alerts
|

Dual HER2 Blockade versus a Single Agent in Trastuzumab-Containing Regimens for HER2-Positive Early Breast Cancer: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Purpose. Although trastuzumab is the standard of care for patients with human epidermal growth factor receptor 2 (HER2)-positive early breast cancer (EBC), drug resistance and disease relapse occur. erefore, we performed a meta-analysis to assess the efficacy and safety of trastuzumab-containing dual anti-HER2 therapy compared to trastuzumab alone. Methods. A systematic search was performed to identify eligible randomized controlled trials (RCTs). Main outcomes including event-free survival/invasive disease-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 57 publications
2
18
0
Order By: Relevance
“…Similar to other studies, our study also demonstrated that dual-target therapy-based regimens are superior to single-target therapy-based regimens. 16 , 57 60 However, the question still remains that which is the best choice among all the dual-target therapies. According to our results, we suggest that the dual anti-HER2 blockade that combines trastuzumab and pertuzumab is better than the combination of trastuzumab and TKIs.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other studies, our study also demonstrated that dual-target therapy-based regimens are superior to single-target therapy-based regimens. 16 , 57 60 However, the question still remains that which is the best choice among all the dual-target therapies. According to our results, we suggest that the dual anti-HER2 blockade that combines trastuzumab and pertuzumab is better than the combination of trastuzumab and TKIs.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the redundancy in signal transduction mediated by the many members of the HER family, incomplete inhibition of the signal can lead to resistance to targeted therapies. To overcome this, a combination of dual TKI lapatinib, or pan-TKI neratinib, plus mAbs has been shown to comprehensively block the known compensatory HER2 signaling network [ 69 , 70 ]. Recently, tucatinib, a highly selective HER2 TKI, has been shown to inhibit HER2/HER3-mediated MAPK and PI3K/AKT signaling [ 71 ].…”
Section: Why Do We Need To Identify Novel Molecular Perturbations?mentioning
confidence: 99%
“…Cetuximab is indicated for the first-line treatment of patients with EGFRexpressing, RAS wild-type (wt) mCRC in combination with FOLFOX; it is administered once a week with an initial dose of 400 mg/m 2 , followed by subsequent doses of 250 mg/m 2 [26]. Previous studies showed the noninferiority of the off-label schedule of cetuximab (500 mg/m 2 , Q2W) compared with the approved schedule [27][28][29].…”
Section: Different Dose Schedules Of Cetuximab In Ras Wild-type Mcrcmentioning
confidence: 99%
“…Pucotenlimab (HX008) is a novel highly selective humanized anti-PD-1 antibody with a S228P hinge mutation and an engineered Fc domain. Pucotenlimab exhibits a decreased antibody-dependent cellular cytotoxicity (ADCC) and a complement-dependent cyto toxicity preventing depletion of PD-1-expressing lymphocytes, while retaining their antitumor activity [26,27].…”
Section: Novel Anti-pd-1 Pucotenlimab In Second Line G/gej Cancermentioning
confidence: 99%